Quantitative study of error dispersion effect in depleting the positional accuracy of cadastral record / Nur Nadhirah Ismail - Ismail, Nur Nadhirah (2024)
In the realm of cadastral measurement, the Certified Plan (CP) stands as the final product from cadastral measurement, providing critical information such as bearings and distances derived through finalizing bearing and distance. However, the final observation yields information in CPs, necessitating the preservation of the positional accuracy of the cadastral record. The goal of this study is to look into this problem more closely by looking at how error propagation affects it and how well the least-squares estimation (LSE) method can handle the differences between the final observations and the ones that were adjusted. This study will employ a method that quantifies the error propagation issues in several CPs and compares the direct versus indirect LSE. The study's goal is to show that using direct measurement (angle) could keep the positional accuracy of cadastral records and reduce the differences between final and adjusted observations with a relatively low increase in error dispersion.